2014
DOI: 10.4000/developpementdurable.10525
|View full text |Cite
|
Sign up to set email alerts
|

Le démantèlement des barrages de la Sélune (Manche). Des réseaux d’acteurs au projet de territoire ?

Abstract: Géohistoire des risques et des patrimoines naturels fluviaux Le démantèlement des barrages de la Sélune (Manche). Des réseaux d'acteurs au projet de territoire ? The removal of two hydroelectric dams of the valley of Selune (Normandy): an unprecedented operation of ecological restoration. The difficult assertion of a new project of territory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Keilty et al (2016) and Fox et al (2016) found that local communities adapt to changes caused by the construction of dams and-in the case of removal-their strong attachment is due to the provision of cultural services (identity, aesthetics, recreation and tourism). Similar findings were made regarding the removal of the 50-year-old Mactaquac dam in Canada (Keilty et al, 2016) and the removal of older dams in France (Germaine & Lespez, 2017),…”
Section: Local Community Versus Water Ecosystems and Infrastructuresupporting
confidence: 77%
See 2 more Smart Citations
“…Keilty et al (2016) and Fox et al (2016) found that local communities adapt to changes caused by the construction of dams and-in the case of removal-their strong attachment is due to the provision of cultural services (identity, aesthetics, recreation and tourism). Similar findings were made regarding the removal of the 50-year-old Mactaquac dam in Canada (Keilty et al, 2016) and the removal of older dams in France (Germaine & Lespez, 2017),…”
Section: Local Community Versus Water Ecosystems and Infrastructuresupporting
confidence: 77%
“…Policies to prevent environmental degradation by restoring the continuity of rivers as ecological corridors have focused attention on dam removal as a method to assist nature (e.g., Duda et al, 2021;Germaine & Lespez, 2017). This is observed in the United States, where more dams are being removed than built, with hydroelectric and water supply dams being the most common types of large dams removed (Grabowski et al, 2018;Waldman et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Lower Normandy, the ecological projects involve both abandoned hydraulic structures and those producing electricity (Germaine and Barraud, 2013a,b). In the Sélune catchment in southwest Lower Normandy, a project will result in the removal of two large dams (heights of 15 and 36 m) in 2016-2017; this is in fact the largest European project in terms of the height of the hydraulic structures (Germaine and Lespez, 2014). In comparison, it is striking to note that in Great Britain, removal operations are most often secondary and reserved for nonoperational works (RRC, 2011(RRC, , 2013.…”
Section: Dam and Weir Removal And Their Geomorphological Effectsmentioning
confidence: 98%
“…foot traffic control) or prohibition of access or a ban on certain local practices, unless dialogue is previously established with stakeholders to reconcile restoration objectives with local practices. Destruction of dams and weirs that entail major landscape changes and destroy connected fishing ponds is another example of a restoration project requiring extensive local dialogue well ahead of realization (Germaine & Lespez ).…”
Section: Barriers To Ecological Restorationmentioning
confidence: 99%